Long-term contracts and efficiency in the liquefied natural gas industry - Nahim Bin Zahur (Queen's University, Department of Economics, 2024)
In many capital-intensive markets, sellers sign long-term contracts with buyers before committing to sunk cost investments. Ex-ante contracts mitigate the risk of under-investment arising from ex-post bargaining. However, contractual rigidities reduce the ability of firms to respond flexibly to demand shocks. This paper provides an empirical analysis of this trade-off, focusing on the liquefied natural gas (LNG) industry, where long-term contracts account for over 70% of trade. I develop a model of contracting, investment and spot trade that incorporates bargaining frictions and contractual rigidities. I structurally estimate this model using a rich dataset of the LNG industry, employing a novel estimation strategy that utilizes the timing of contracting and investment decisions to infer bargaining power. I find that without long-term contracts, sellers would decrease investment by 27%, but allocative efficiency would significantly improve. Negative contracting externalities lead to inefficient over-use of long-term contracts in equilibrium. Policies aimed at eliminating contractual rigidities reduce investment by 16%, but raise welfare by 9%.
Keywords: D22; D23; L14; L22; L42; Q41; 330; Long-term Contracts; Spot Markets; Under-investment; Nash Bargaining; ContractingExternalities; Market Power; Liquefied Natural Gas